(untitled) (Transport systems and technologies, 2021)
The article examines the residual life of load-bearing metal structures (NMC) of special cars for the transportation of special contingent on the basis of the results of technical diagnostics and standard tests. Most scientific publications investigate the increase in the service life of different types of passenger cars by improving their design properties. The following methods are used in the study: resetting from wedges, resource tests for impact strength, impact tests, static strength tests. On the basis of carrying out technical diagnostics and standard tests the possibility of establishment of new appointed service life of cars is defined. The residual resource was set at one of the minimum calculated values obtained by mathematical dependence to calculate the residual service life. When determining the residual resource during the standard tests, the evaluation of the fatigue resistance margin was performed taking into account the stress of the load-bearing structures of the car during the tests. It is concluded that the condition of load-bearing metal structures of special wagons for transportation of special contingent after long operation does not approach the limit. The obtained practical and theoretical results make it possible to extend the service life of special wagons for the transportation of special contingent beyond the established by the manufacturer.